Inhibition of osteoblast activity by zoledronic acid - Basso, Fernanda Gonçalves (2013)
INTRODUCTION: Patients treated with nitrogen-containing bisphosphonates, such as zoledronic acid (ZA), have frequently shown oral bone exposure areas, termed osteonecrosis. In addition, these patients may also present low repair and regeneration potential, mainly after tooth extractions. These side-effects caused by bisphosphonates may be due to their inhibitory effects on oral mucosa and local bone cells. OBJECTIVE: To evaluate the effects of ZA on the mineralization capacity of cultured osteoblasts. MATERIALS AND METHODS: Human immortalized osteoblasts (SaOs-2) were grown in plain culture medium (Dulbecco's Modified Eagle Medium [DMEM] + 10% fetal bovine serum [FBS]) in wells of 24-well plates. After 48-hour incubation, the plain DMEM was replaced by a solution with ZA at 5 µM which was maintained in contact with cells for seven, 14 or 21 days. After these periods, cells were evaluated regarding alkaline phosphatase (ALP) activity and mineral nodule formation (alizarin red). Data were statistically analyzed by Mann-Whitney test, at 5% of significance level. RESULTS: ZA caused significant reduction on ALP activity and mineral nodules formation by cultured osteoblasts in all evaluated periods (p < 0.05). CONCLUSION: These data indicate that ZA causes inhibition on the osteogenic phenotype of cultured human osteoblasts, which, in turn, may reduce bone repair in patients subjected to ZA therapy.